PEMBENTUKAN KARAKTER RELIGIUS, DISIPLIN DAN TANGGUNGJAWAB MELALUI KEGIATAN TAHFIDZUL QUR’AN DI SD ISLAM ROUSHON FIKR JOMBANG - Wahyu Basuki Rahmad; Asriana Kibtiyah (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2022)
This study uses a descriptive qualitative approach with case study research, data collection techniques using observation, interviews, and documentation. Data analysis techniques through data reduction, data presentation and drawing conclusions. Checking the validity of the data is done through credibility, transferability, dependability, and confirmability. From the results of the study, it can be seen that first, the activities of tahfidzul Qur'an, among others: 1) Planning of learning activities for tahfidzul Qur'an; 2) implementation of tahfidul Qur'an learning, 4) Class management, and 5) Evaluation of learning outcomes. Second, the formation of the religious character of students' discipline and responsibility through tahfidzul Qur'an activities, including: 1) Religious; Perform ablution before reading and memorizing the Qur'an, saying greetings and reading prayers, and students are serious about memorizing, 2) Discipline; enter the classroom in an orderly and timely manner, then students queue when the tahfidz teacher listens to other students. and 3) responsibility; daily memorization deposit and doing assignments from the tahfidz teacher. Third, the inhibiting factors for the formation of disciplined and responsible religious character through tahfidzul Qur'an activities, 1) Religious; less than maximum deposit hours, himma (less will to memorize), 2) discipline; there are often delays in going to school or delays in depositing the specified memorization. 3) responsibility; The lazy nature that exists in students not to carry out rote memorization. and supporting factors for character building through tahfidzul Qur'an activities, including: Religious; create a sense of love for the Koran in students, familiarize students independently memorize the Koran, and increase students' motivation to memorize. 2) Discipline; build a culture of reading the Qur'an at school, requiring students to muroja'ah every day, and exemplary from teachers, and 3) Responsibility, providing targets for memorizing the Qur'an, as well as giving assignments to students.